2018
DOI: 10.3390/catal8040125
|View full text |Cite
|
Sign up to set email alerts
|

Active Component Migration and Catalytic Properties of Nitrogen Modified Composite Catalytic Materials

Abstract: During the catalytic combustion reaction of methane, the migration of the active species on surface facilitates the catalytic reaction, and the element doping can improve the redox performance of the catalyst. Nitrogen-modified perovskite type composite catalysts were prepared by hydrothermal method and then characterized by X-ray diffractometer (XRD), scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET), temperature-programmed reductions (TPR), and X-ray photoelectron spectra (XPS). The results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Elements like Ca and Mg are often used as promoters, while Ce and Mn are doped to obtain oxygen vacancies ( Pecchi et al, 2011 ; Chen Y. L. et al, 2021 ). N is a commonly used dopant in non-metal doping, which can create more lattice distortions and further increase active oxygen species ( Buchneva et al, 2012 ; Li et al, 2018 ).…”
Section: Reaction Fundamentalsmentioning
confidence: 99%
“…Elements like Ca and Mg are often used as promoters, while Ce and Mn are doped to obtain oxygen vacancies ( Pecchi et al, 2011 ; Chen Y. L. et al, 2021 ). N is a commonly used dopant in non-metal doping, which can create more lattice distortions and further increase active oxygen species ( Buchneva et al, 2012 ; Li et al, 2018 ).…”
Section: Reaction Fundamentalsmentioning
confidence: 99%
“…Banerjee et al [15] compared the relative efficiencies of Pd/alumina catalysts prepared by the vortex and incipient wetness methods. The catalyst synthesized by the vortex method produced smaller PdO/PdOx nanoparticles (2-5 nm) and converted 90% methane at 325 • C. Li et al [16] reported nitrogen-modified perovskite type composite catalysts prepared by a hydrothermal method for catalytic oxidation of methane. The surface reaction mechanism was investigated using in-situ diffuse reflectance infrared Fourier transform spectroscopy.…”
Section: The Special Issuementioning
confidence: 99%
“…A Pd/Ceria nanocatalyst on Al 2 O 3 support was prepared by solution combustion method with 90% methane conversion at 400 • C [13]. A nanozeolite silicalite-1 coated cordierite catalyst and a nitrogen-modified perovskite-type composite catalyst eliminated 90% methane at 350 • C [14,15]. A Pd/Co 3 O 4 catalyst on ZrO 2 open cell foam converted about 90% methane at 325 • C and 100% at 400 • C [16].…”
Section: Introductionmentioning
confidence: 99%